2013
DOI: 10.1002/phar.1287
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hospital Admissions Associated with Adverse Drug Events

Abstract: Adverse drug events are an important cause of hospital admission. Better systems for health care practitioners to identify patients at high risk of preventable hospital admissions associated with ADEs (e.g., age > 65 years old, receiving more than five drugs, and starting new high-risk drugs) should be implemented in order to minimize the risks to patients and the burden on the health care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 35 publications
5
73
2
2
Order By: Relevance
“…This finding was supported by previous results. 19 Our study results also revealed that oral hypoglycemics are the second categories of drugs that have caused ADR related hospital admission. Larger number of diabetic patients in our study population and poor awareness of patients with regard to hypoglycaemic symptoms might be plausible explanation for increased ADRs observed with oral hypoglycaemic drugs.…”
Section: Adverse Drug Reactionsmentioning
confidence: 56%
See 1 more Smart Citation
“…This finding was supported by previous results. 19 Our study results also revealed that oral hypoglycemics are the second categories of drugs that have caused ADR related hospital admission. Larger number of diabetic patients in our study population and poor awareness of patients with regard to hypoglycaemic symptoms might be plausible explanation for increased ADRs observed with oral hypoglycaemic drugs.…”
Section: Adverse Drug Reactionsmentioning
confidence: 56%
“…Similar to our findings, previous results demonstrate that 7.1% of hospital admissions result from DRPs, of which 59% were deemed preventable. 29,30 On the other hand, A Scottish paper, based on the same methodology, reported that only 13.3% of admissions were unavoidable. 31 Several other studies have reported similar findings with 60-70% of ADRs being classes as preventable.…”
Section: Preventabilitymentioning
confidence: 99%
“…However, studies in inpatient settings demonstrate that 10% of patients are admitted to hospital due to adverse drug events and approximately 5% of these are preventable medicines-related issues 4. Furthermore, medication errors are one of the leading causes of injury to hospital patients, and medication chart reviews reveal that over half of all hospital medication errors occur at the interfaces of care 12.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a significant number of medicines-related incidents occur when patients transfer between care settings 2. The literature suggests that 6%–10% of admissions have a medicines-related contribution due to adverse drug events 3 4. Hospitals in the UK are expected to comply with relevant standards5 and guidance 2.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that antiplatelet, anticoagulants, diuretics, and NSAIDs (non-steroidal anti-inflammatory drugs) are responsible for more than half of the preventable drug-related admissions to hospital [13,14]. Elderly patients also have a high risk of drug-related problems, such as delirium or renal failure, with an increasing number of medications [15].…”
Section: Introductionmentioning
confidence: 99%